Flipbook vs Presentation Media: Revisiting Empirical Studies and Literature Review in Islamic Education - Miftah Hur Rahman ZH; Dedi Kuswandi; Muhibuddin Fadhli (Dinasti International Journal of Education Management And Social Science, 2025)
The rapid advancement of technology has profoundly influenced educational practices, particularly within the domain of Islamic education. The inherent complexity of Islamic Education (PAI) presents unique challenges for educators in selecting the most effective instructional media to facilitate learning. This study investigates the integration of technology in Islamic education, with a specific focus on the use of flipbooks and PowerPoint as instructional tools. Employing the PRISMA-based Systematic Literature Review (SLR) methodology, this research compiles and analyzes prior studies on the application of these two media in Islamic education contexts. This approach provides a structured and comprehensive insight into the effectiveness of instructional media in enhancing teaching quality. The findings reveal that utilizing flipbooks for content requiring deep comprehension, alongside PowerPoint for presenting well-structured information, significantly improves the overall learning experience. Moreover, regular evaluation of media usage by educators is essential to ensure their continued relevance and efficacy in achieving pedagogical objectives. The study further underscores the importance of tailoring media selection to students' learning styles—whether visual, auditory, or kinesthetic—to maximize learning outcomes. In conclusion, this research emphasizes the critical role of technology in Islamic education, advocating for an approach that considers student characteristics and instructional contexts in the digital era to foster an optimal learning experience.